Segmental volume reduction using thermal vapour ablation in patients with severe emphysema: 6-month results of the multicentre, parallel-group, open-label, randomised controlled STEP-UP trial - Herth, Felix; Valipour, Arschang; Shah, Pallav; Eberhardt, Ralf; Grah, Christian; Egan, Jim; Ficker, Joachim H; Wagner, Manfred; Witt, Christian; Liebers, Uta; Hopkins, Peter; Gesierich, Wolfgang; et al. (The lancet. Respiratory medicine, 2016)
Background - Lung volume reduction of emphysematous lobes results in clinical improvement for patients with severe emphysema. However, some segments within a lobe are often substantially more diseased than others, thereby warranting a more targeted approach of the emphysematous parts of a lobe. We therefore did a study to assess whether or not selective sequential treatment of the more diseased upper lobe segments with bronchoscopic vapour ablation led to clinical improvement. - Methods - For the multicentre, parallel-group, randomised, controlled, open-label Sequential Staged Treatment of Emphysema with Upper Lobe Predominance (STEP-UP) trial, adult patients aged 45-75 years with severe, upper lobe-predominant emphysema with a forced expiratory volume in 1 s (FEV1) between 20% and 45%, substantial hyperinflation, and post-rehabilitation 6-min walk test (6MWT) greater than 140 m were enrolled from 13 hospital sites in Europe (ten sites) and Australia (three sites). A computer-generated blocked randomisation scheme (block size three per site based on a random table from an independent biostatistician) stratified by site was used to randomly assign enrolled patients 2:1 to segmental vapour ablation (treatment group) or standard medical management (control group). Patients and investigators were not masked to group assignment. The primary efficacy endpoints were statistically significant changes in FEV1 and St George's Respiratory Questionnaire (SGRQ-C) scores between trial groups at 6 months, analysed by intention to treat. This study is registered with ClinicalTrials.gov, number NCT01719263. - Findings - Between June 30, 2013, and Oct 1, 2014, 134 patients were screened and 70 were enrolled and randomly assigned: 46 to the treatment group and 24 to the control group. One patient in the treatment group did not receive treatment because of physician decision post-randomisation; this patient is excluded from all analyses. The mean relative improvement in FEV1 between the treatment group versus the control group was 14·7% (95% CI 7·8-21·5%; p<0·0001) and in SGRQ-C was −9·7 points (95% CI −15·7 to −3·7; p=0·0021). COPD exacerbation was the most common serious adverse event, occurring in 11 (24%) of 45 patients in the treatment group and one (4%) of 24 in the control group. One exacerbation resulted in a patient death 84 days after treatment; this was judged by the data and safety monitoring board to be possibly related to treatment. No pneumothorax occurred within 30 days of treatment. - Interpretation - Compared with standard medical management, targeted thermal vapour ablation of more diseased segments and preservation of less diseased segments resulted in clinically meaningful and statistically significant improvements in lung function and quality of life at 6 months, with an acceptable safety profile. - Funding - Uptake Medical.
Gesehen am 11.03.2020